Field Investigation on Sub-clinical Mastitis in Cows in Different areas of Barisal district in Bangladesh - Mirza Mienur Meher; Aliul Hasan; Marya Afrin (Turkish Journal of Agriculture: Food Science and Technology)
In every year, Subclinical mastitis (SCM) frequently occurs and results huge economic losses in livestock industry of Bangladesh. This study was redacted to estimate the present status of SCM in cow in selective area of Barisal district. For determining sub-clinical mastitis, a total of 152 milk samples of clinically suspected cows were subjected to White Side Test (WST) and Surf Field Mastitis Test (SFMT). Specifically, the milk samples of each individual cows which were positive to both WST and SFMT considered as SCM indicating 35.52% prevalence. Other than the local breed cows, the cross bred cows showed significantly higher prevalence, is 47.06%. In consideration to age variation, highest prevalence was observed at 5 to 7 years of age in both types where cross breed was 54.71% and 36.67% for local breed cows. Though highest prevalence was recorded as 34.78% in 2nd parity of local breed cows but the cross breed cows showed highest prevalence 54.55% in their 3rd parity. Afterward, non-pregnant cows showed the insignificantly higher prevalence (41.06%) than pregnant cows were 26.32%. Additionally, this study reported that the cross breed cows yielding more than 10 liters of milk (prevalence was 61.54%) were more prone to SCM than the others and also >5 to 10 liters milk producing local breed cows (prevalence was 31.03%) were more susceptible to SCM than others. In a short, this study revealed that high milk yielding cross breed cows are more likely to SCM after their 3rd calving.